2015
DOI: 10.1515/res-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Washing, Spraying and Brushing. A Comparison of Paper Deacidification by Magnesium Hydroxide Nanoparticles

Abstract: AbstractThe paper presents the results of studies on the deacidification of model papers (Whatman) using nanodispersions of magnesium hydroxide in 2-propanol. Preliminary experiments showed greater effectiveness of nanodispersion deacidification in comparison with the standard magnesium hydroxide reagent which was applied in the form of micrometric particles. Further analyses compared the effectiveness of deacidification by washing, spraying and brushing. Although all of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…For mechanized, mass-deacidification treatment, Wagner et al (2008) observed a suitably uniform distribution of particles, from the perspective of the surface of the paper, based on imaging with laser ablation inductivity coupled plasma mass spectroscopy. Wojciak (2015) found that a more uniform distribution can be achieved by using nano-sized particles. Zumbühl and Wuelfert (2001) evaluated the role of perfluorinated dispersants employed in a major non-aqueous dispersion deacidification program.…”
Section: Particle Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…For mechanized, mass-deacidification treatment, Wagner et al (2008) observed a suitably uniform distribution of particles, from the perspective of the surface of the paper, based on imaging with laser ablation inductivity coupled plasma mass spectroscopy. Wojciak (2015) found that a more uniform distribution can be achieved by using nano-sized particles. Zumbühl and Wuelfert (2001) evaluated the role of perfluorinated dispersants employed in a major non-aqueous dispersion deacidification program.…”
Section: Particle Distributionmentioning
confidence: 99%
“…nanoparticles. Thus, it has been proposed to deacidify paper by addition of nano-sized Ca(OH)2 (Giorgi et al 2002;Sequeira et al 2006;Stefanis and Panayiotou 2007), or Mg(OH)2 (Giorgi et al 2005;Stefanis and Panayiotou 2007;Giorgi 2015;Amornkitbamrung et al 2015;Wojciak 2015). More research is needed to follow up in this area.…”
Section: Nanoparticles Added While Completing Deacidificationmentioning
confidence: 99%
“…Also, there seems to be a slight reduction in the paper’s basis weight of the treated supports compared to B1, which could further sustain the washing effect of the ILs on paper. However, other mechanisms may also contribute to the deacidification effect, such as the hydrogen bonding between ILs and cellulose, which may alter the acidity and basicity of the hydroxyl groups, and the other types of interactions between ILs and paper, such as electrostatic, van der Waals, or π–π stacking interactions, which may influence the solubility and stability of paper components [ 36 , 40 ]. The ILs used in this study have the same anion, and similar cations, which are N-alkyl-N′-methylimidazolium derivatives with different alkyl chain lengths.…”
Section: Resultsmentioning
confidence: 99%
“…Anguera [32] 报道了半饱和氢氧化钙与碳酸氢盐(碳酸氢 镁、 碳酸氢钙)混合溶液对纸张的脱酸. 张等 [50] a [47] S1 BSP 浸泡 Ca(OH) 2 水 b [48] Whatman paper…”
Section: 微纳米粒子形态脱酸材料unclassified